Computer-aided drug discovery approach finds calcium sensitizer of cardiac troponin - Lindert, Steffen (Chem Biol Drug Des, 2014)
In the fight against heart failure, therapeutics that have the ability to increase the contractile power of the heart are urgently needed. One possible route of action to improve heart contractile power is increasing the calcium sensitivity of the thin filament. From a pharmaceutical standpoint, calcium sensitizers have the distinct advantage of not altering cardiomyocyte calcium levels and thus have lower potential for side effects. Small chemical molecules have been shown to bind to the interface between cTnC and the cTnI switch peptide and exhibit calcium sensitizing properties, possibly by stabilizing cTnC in an open conformation. Building on existing structural data of a known calcium sensitizer bound to cardiac troponin, we combined computational structure-based virtual screening drug discovery methods and solution NMR titration assays to identify a novel calcium sensitizer 4-(4-(2,5-dimethylphenyl)-1-piperazinyl)-3-pyridinamine (NSC147866) which binds to cTnC and the cTnC-cTnI(147-163) complex. Its presence increases the affinity of switch peptide to cTnC by approximately a factor of two. This action is comparable to that of known levosimendan analogues.